Effects of mind-body practice on arterial stiffness, central hemodynamic parameters and cardiac autonomic function of college students. (November 2021) - Cai, Li; Huang, Junhao; Gao, Dongdong; Zeng, Shujuan; Tang, Songxin; Chang, Zhengxiao; Wen, Caosheng; Zhang, Meina; Hu, Min; Wei, Gao-Xia
Abstract: A substantial number of studies have shown the beneficial effects of mind-body practice on physical fitness among both the healthy middle-aged and elderly adults and patients with chronic diseases. However, its positive effects on college students remain poorly understood. This study aimed to systematically investigate the potential efficiency of the Baduanjin exercise on the maintenance of the homeostasis of body composition and the improvement of the cardiovascular function of the college students. The study revealed a promising efficacy of the Baduanjin exercise in the prevention of the loss of water, inorganic salts, protein, and muscle contents and the accumulation of body fat. Furthermore, the present study also demonstrated the positive efficacy of Baduanjin exercise in decreasing of peripheral and central arterial blood pressure and carotid and femoral artery pulse wave velocity (cfPWV) of the college students. Moreover, the heart rate variability (HRV) analysis was also performed using the assessment of time and frequency domain indices. The data showed that all of the time-domain indices and the high-frequency (HF) band of the HRV relatively increased, whereas the low-frequency (LF) band of the HRV relatively decreased after the long-term Baduanjin exercise. Collectively, the present study suggested that a 12-week Baduanjin exercise could maintain the body composition in a relatively healthy and stable range and improve blood pressure, central hemodynamics, and the arterial stiffness of the college students. The underlying mechanism might be due to the improvement of parasympathetic activity and the suppression of sympathetic activity of college students via Baduanjin exercise.